2018
DOI: 10.1371/journal.ppat.1007182
|View full text |Cite
|
Sign up to set email alerts
|

Chronic schistosomiasis suppresses HIV-specific responses to DNA-MVA and MVA-gp140 Env vaccine regimens despite antihelminthic treatment and increases helminth-associated pathology in a mouse model

Abstract: Future HIV vaccines are expected to induce effective Th1 cell-mediated and Env-specific antibody responses that are necessary to offer protective immunity to HIV infection. However, HIV infections are highly prevalent in helminth endemic areas. Helminth infections induce polarised Th2 responses that may impair HIV vaccine-generated Th1 responses. In this study, we tested if Schistosoma mansoni (Sm) infection altered immune responses to SAAVI candidate HIV vaccines (DNA and MVA) and an HIV-1 gp140 Env protein v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 92 publications
3
23
0
Order By: Relevance
“…Although a one-time praziquantel treatment in our study did not alter the elevated levels of α4β7, the transcriptome analysis indicated that Sm treatment was associated with changes in expression of multiple other integrins by blood mononuclear cells, including α2, αE and αM (see Supplementary Note 5), suggesting treatment-induced reprogramming of cell homing in agreement with studies in murine models of schistosomiasis 41 . Given that schistosomiasis-associated pathological changes are not reversed up to six months post-treatment 42 and eggs retained in tissues continue to exert negative immune effects after chemotherapy 43 , it is perhaps unsurprising that we saw only partial restoration of immune function in our study. Future research will need to assess these parameters at later time points to understand the longer-term effects of schistosomiasis therapy on HIV susceptibility and antiviral defenses.…”
Section: Discussionmentioning
confidence: 69%
“…Although a one-time praziquantel treatment in our study did not alter the elevated levels of α4β7, the transcriptome analysis indicated that Sm treatment was associated with changes in expression of multiple other integrins by blood mononuclear cells, including α2, αE and αM (see Supplementary Note 5), suggesting treatment-induced reprogramming of cell homing in agreement with studies in murine models of schistosomiasis 41 . Given that schistosomiasis-associated pathological changes are not reversed up to six months post-treatment 42 and eggs retained in tissues continue to exert negative immune effects after chemotherapy 43 , it is perhaps unsurprising that we saw only partial restoration of immune function in our study. Future research will need to assess these parameters at later time points to understand the longer-term effects of schistosomiasis therapy on HIV susceptibility and antiviral defenses.…”
Section: Discussionmentioning
confidence: 69%
“…Eight animal studies reported decreased Th1 and increased Th2/T reg responses to HIV during schistosome infection [ 55 62 ]. In the first, splenocytes from S .…”
Section: Resultsmentioning
confidence: 99%
“…Murine models have also displayed reduced vaccine efficacy following schistosoma infection, for example, against Mycobacterium tuberculosis (51), reducing type 1 responses typified by IFN-γ and instead increasing type 2 responses. Recently, experimental murine S. mansoni infection inhibited effective cellular and antibody responses against novel HIV vaccines, with even the presence of schistosoma eggs alone (as a result from de-worming) able to reduce humoral vaccine responses (52). Nevertheless, effects of antihelminthic treatment on vaccine efficacy in human cohorts remains unclear (53, 54).…”
Section: Effects Of Maternal Schistosomiasis On Vaccine Efficacy In Omentioning
confidence: 99%